Determinants of Financial Inclusion in Africa: Evidence on Bank account ownership - (:unkn) unknown (My University, 2018)
The term "financial inclusion" implies the access to and use of banking services (bank accounts, savings, insurance, credits, payments, etc.) at a low cost for disadvantaged and low-income population in a country. In fact, banking services are considered as a public good. It is therefore necessary that the accessibility and equity in the use of banking services by the entire population must be among the main objectives of government policies and financial institutions, for it helps to meet the basic financial needs of the population in any country. The main objective of our study is to examine the determinants of bank account ownership which is considered to be the basic dimension of banking services use and therefore financial inclusion. In our paper, adopting an empirical approach of cross-sectional data, we study the elements that condition the ownership of a bank account in the African continent.
Keywords: African Research